Tadlis in Islamic transactions / Mohamed Azam Mohamed Adil … [et al.] - Mohamed Adil, Mohamed Azam; Muhamad, Mohd Dani; Yaakub, Ezani; Ishak, Amal Hayati (Universiti Teknologi MARA Cawangan Selangor, 2010)
The discussion on tadlis has been quite complicated since Muslim jurists are in dispute over its meaning. Some tend to interchange it with taghrir and ghabn. While others suggest that the doctrine of tadlis and misrepresentation are so closely interrelated. This article suggests that the doctrine of tadlis is so akin to taghrir and ghabn which mean fraud. It also suggests that the effect of fraud in Islamic transactions is that the defrauded party may rescind the contract by exercising the option of fraud (khiyar al-tadlis).